Poet-Literary Critic (Vahagn Davtyan - 100) - Kalantaryan, Zhenya (Bulletin of Yerevan University B: Philology, 2023)
The article discusses Armenian poet Vahagn Davtyan’s critical articles, where he both discusses the work of Armenian and non-Armenian writers (poets), and explores general theoretical issues. Those questions refer to the essence of poetry, the organic connection between tradition and innovation, the national nature of literature, the problem of translation, etc. Davtyan’s articles are twofold, because on the one hand, they reveal the character of an individual writer, and on the other, discuss general literary patterns.
Keywords: Poetry; harmony; subconsciousness; landscape; tradition; innovation; national; universal; standard; translation